2023
DOI: 10.1037/pspp0000451
|View full text |Cite
|
Sign up to set email alerts
|

Parenting orientations in young adulthood: Predicting timing of parenthood and quality of postpartum caregiving.

Abstract: Most but not all adults become parents, yet it remains unclear which characteristics indicate an orientation toward parenting. The aims of this study were to (a) distinguish profiles of individual and interpersonal resources in young adults that may orient them toward parenthood and (b) investigate whether profiles predicted timing of entering parenthood, postpartum parenting behavior, and parent–infant bonding. Participants were 1,429 young people (53% female) enrolled in an Australian 39-year longitudinal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Given the considerable success that initiatives such as Men's Shed have had with older Australian men (Kelly et al, 2021), there may also be profound benefits in developing social initiatives that specifically cater to men in 'established adulthood' who are typically time pressed at this developmental life stage (Mehta et al, 2020). Furthermore, this life stage is commonly characterised by a deepening of commitment to partners, children and/or career, and so, there are likely additional cascading benefits into these life domains from interventions that strengthen men's social connections (Macdonald et al, 2023). Our study also highlights the potential for sporting or social physical activity memberships to be useful for supporting concurrent mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Given the considerable success that initiatives such as Men's Shed have had with older Australian men (Kelly et al, 2021), there may also be profound benefits in developing social initiatives that specifically cater to men in 'established adulthood' who are typically time pressed at this developmental life stage (Mehta et al, 2020). Furthermore, this life stage is commonly characterised by a deepening of commitment to partners, children and/or career, and so, there are likely additional cascading benefits into these life domains from interventions that strengthen men's social connections (Macdonald et al, 2023). Our study also highlights the potential for sporting or social physical activity memberships to be useful for supporting concurrent mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Fathers may have been disproportionally represented in the emotion coaching profile as a result of measurement bias. Research has suggested that self-report measures of empathy are influenced by gender expectations and biases, thus do not adequately capture empathy of fathers ( Baez et al, 2017 ; Macdonald et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%